2012
DOI: 10.1016/j.jcin.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Prasugrel Versus Tirofiban Bolus With or Without Short Post-Bolus Infusion With or Without Concomitant Prasugrel Administration in Patients With Myocardial Infarction Undergoing Coronary Stenting

Abstract: Our study shows that prasugrel administration leads to a suboptimal IPA for at least 2 h in STEMI patients. Yet, prasugrel, given in association with a bolus only of glycoprotein IIb/IIIa inhibitor, obviates the need of post-bolus infusion and almost completely abolishes residual variability of IPA after treatment. (Facilitation through Aggrastat By drOpping or shortening Infusion Line in patients with ST-segment elevation myocardial infarction compared to or on top of PRasugrel given at loading dOse [The FABO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(43 citation statements)
references
References 20 publications
1
39
0
3
Order By: Relevance
“…30 In addition, combining the GPIIb/IIIa inhibitor tirofiban with prasugrel nearly completely abolishes residual variability in platelet aggregation inhibition. 31 Moreover, the direct thrombin inhibitor bivalirudin with prasugrel is more effective in patients with STEMI. 32 Although these intravenous agents are not affected by impaired drug absorption, they are not available in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, combining the GPIIb/IIIa inhibitor tirofiban with prasugrel nearly completely abolishes residual variability in platelet aggregation inhibition. 31 Moreover, the direct thrombin inhibitor bivalirudin with prasugrel is more effective in patients with STEMI. 32 Although these intravenous agents are not affected by impaired drug absorption, they are not available in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…These groups of investigators have drawn on pharmacological principles and have argued that routine glycoprotein IIb/IIIa infusion is unnecessary because the antiplatelet effects of the bolus last for ≈2 hours and overlaps with the oral antiplatelet agents that are routinely administered before or immediately after the completion of PCI. Recent work by Valgimigli et al 26 demonstrating rapid and sustained inhibition of platelet aggregation by a combination of high-dose tirofiban bolus and oral prasugrel provides support for this argument. Second, the bolus-only group may avoid the risk of delayed bleeding seen with the standard therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Angiolillo et al3 showed that in P2Y 12 ‐naïve patients with unstable angina, the rate of HPR with ticagrelor was still high at 2 hours. Likewise, Valgimigli et al14 showed that IPA with prasugrel and tirofiban bolus or 2‐hour infusion was significantly higher than prasugrel alone in patients with ST‐segment elevation myocardial infarction. Furthermore, the ATLANTIC trial15 demonstrated that the prehospital administration of ticagrelor did not improve pre‐PCI coronary reperfusion because maximal IPA with ticagrelor did not occur until 1 hour post‐PCI.…”
Section: Discussionmentioning
confidence: 97%